A Schema for a Natural Ontology of the Human: Reflections on Psychology and Religion - Feldstein, Leonard C (Journal of Dharma, 1983)
In its broadest meaning, psychology refers to the movements of the human soul : their vicissitudes, their origins, their fate. In contemporary usage, it suggests only the structures of mind in a scientific sense; it deals with such techniques as fix mind's contents and prero• gatives. Wide-ranging and soaring, the soul animates everything we call human. As the soul's mere residue, mind, however has but a restricted set of functions investigable as a behavioural phenomenon. In its original sense, religion means a durable binding : firm, unbreakable commitment, ground for personal salvation, locus of ultimate responsibility. More narrowly, it refers to ritual and dogma, and to prescribed habits of worship. In this essay, I propose certain links between religion and psychology, intending these terms in their larger import. Such comprehensive psychology studies mankind's adventure toward some over-arching, all-inclusive concern. In the religious orientation, this process culminates in the fruition of all aspiration, as a redeeming participation in something beyond the natural.